Багатокритеріальна оптимізація критеріїв транспортної телекомунікаційної мережі - Щербакова, Л.О. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
Designing communication networks is a complex, multiconstraint and multi-criterion optimization problem. We present a multi-objective optimization approach to setting up a network while simultaneously minimizing network overloads and installation costs subject to reliability and flow constraints. These multi-criteria problems place great demands on mathematical formulation and method. In the literature different approaches for solving these kinds of multicriteria problems can be found, whereby two basic approaches are distinguished. On the one hand there are aggregation methods, e,g, the weighted sum function and the search for an object function, and on the other hand there are the so-called Paretobased solution techniques. In this article Pareto-based solution techniques are presented.